Evaluation Au Laboratoire De L’efficacite De La Peinture Insecticide Acrylique Titan® Contre Anopheles Gambiae, Vecteur Majeur Du Paludisme En Côte d’Ivoire - Emmanuel, Tia; Guillaume, Konan Koffi; Anne Marie, Boby Ouassa; Kone, Moussa; Alex, Tea Sea; Bernard, Koffi; Kouamé, Kadjo (European Scientific Journal, ESJ, 2016)
Malaria is by far the most important vector disease. The word strategy of control of the vectors of that disease is based mainly on the use of the impregnated insecticide mosquito nets of long life action (MILDA). Unfortunately the effective use rate of MILDA remains still weak. To mitigate this handicap, it is necessary to identify complementary methods of vectors control of which the use of insecticidal paint. The objective of this study is to evaluate the entomological effecacy of insecticide paint TITAN containing deltaméthrine 0.07% against Anopheles gambiae, main malaria vector in Côte d’Ivoire. The Method used in this study comprised the setting in contact between that insect with cement and wood substrates treated with insecticidal paint in WHO cones and tunnels. The rates of mosquitos Knocked-down (KD) recorded varied from 93 to 97% respecting the threshold fixed by WHO (95%) in contact with painted wood and cement. Moreover, this paint induced a reduction of 94% of the blood meal of the mosquitoes on the guinea-pigs. However, the lethal properties of this paint on the studied insect varying from 51 to 77.50%, are still slightly under the standard of WHO (80%). We can deduce from these results that the insecticide paint TITAN is effective against the sensitive strain of Anopheles gambiae, by considering its excito-repulsive properties (shock effect) and its capacity to reduce the blood meal of blood of the that vector. The improvement of its lethal virtues by an increase of the concentration in deltaméthrine of this paint from 0.07% to 1%, as recommended on the impregnated mosquito nets, will increase this efficacy and would more facilitate its acceptance by the populations. A study of the remanence of the paint and its experimentation on the field must be carried out in order to have complementary data on the effectiveness of TITAN painting.